Evaluation of the in vitro and in vivo metabolic pathway and cytochrome P450 inhibition/induction profile of Huperzine A - Lin, Ping-ping; Li, Xue-ning; Yuan, Fei; Chen, Wei-li; Yang, Meng-jie; Xu, Hong-rong (Biochemical and biophysical research communications, 2016)
Huperzine A (HupA), one of the reversible and selective acetylcholinesterase inhibitors derived from Chinese herb Huperzia Serrata, possesses affirmative action of ameliorating cognitive dysfunction of Alzheimer's disease. Up to now, the effects of HupA on human cytochrome P450s (CYPs) have not been fully elucidated. The purpose of the present study was to clarify the metabolic pathway of HupA in vitro and in vivo, and to evaluate the CYPs inhibition/induction profile of HupA in vitro. The catalytic activity of CYP enzymes (CYP1A2, 2A6, 2C9, 2C19, 2D6, 2E1 and 3A4) was measured by the quantification of specific enzyme substrates using validated liquid chromatography-tandem mass spectrometry (LC/MS/MS) methods. The in vivo metabolic pathway evaluation was performed in an open, single-dose pharmacokinetic study of HupA in fourteen elderly subjects, with urine collecting at certain intervals. In human liver microsomes, HupA (10 ng/mL) was not metabolized within 90 min, and it showed negligible inhibition against these CYP isoforms within 0.2–100 ng/mL. In human liver hepatocytes, the activities of CYP1A2 and CYP3A4 were not significantly altered when incubated at 2 or 20 ng/mL of HupA. After oral administration of 0.1 mg HupA, the total proportion of HupA excreted through urine was relatively high, accounting to 35± 9% at the limited time period of 48 h. These results suggest that HupA is substantially excreted by kidney unchanged rather than metabolized by human liver, and is unlikely to cause clinically relevant drug-drug interaction (DDI) when co-administrated with drugs that are metabolized by CYP isoenzyme system. [Display omitted] •HupA can be hardly metabolized by human liver microsomes.•HupA was predominately eliminated from renal excretion unchanged.•HupA is unlikely to cause DDI when used with drugs metabolized by CYPs system.•Attention should be paid when HupA is taken together with drugs excreted from kidney.